Upaya Penanggulangan Pernikahan Dini Bagi Masyarakat di Desa Lawang Agung Kecamatan Kedurang Bengkulu Selatan - Histidiana, Veter; Dihamri; Zairin (Universitas Prof. Dr. Hazairin, S.H, 2024)
The focus of this research is to find out the efforts made by the community to overcome early marriage in Lawang Agung Village. Adapuan The aim of the research is to find out how efforts are made to overcome early marriage in Lawang Agung Village. The method used is a qualitative method. The informants that the researcher took in This research consisted of ten people consisting of husband and wife couples who had legally entered into an early marriage, community leaders (village head, traditional leaders, religious leaders, village midwife) and the community in Lawang Agung village. Data collection was carried out by observation, interviews, and documentation. The data obtained was analyzed by data reduction, data presentation and drawing conclusions. The research results show that the community in Lawang Agung Village has made various efforts to prevent early marriage by carrying out various efforts, such as: 1. Socialization regarding the negative effects of early marriage. Socialization has been carried out through youth posyandu. counseling about the health of childbearing age and the dangers of early marriage. However, socialization has not been carried out thoroughly. 2. Efforts to prevent early marriage for the community in Lawang Agung village.